2015
DOI: 10.14432/j.macvetrev.2014.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Myxomatous Mitral Valve Disease in Dogs - an Update and Perspectives

Abstract: Myxomatous mitral valve disease is a common cause of congestive heart failure in geriatric dogs. Many studies have been done in terms of epidemiology, pathology, associated neurohormonal changes in the disease progression, prognostic factors, and survival and treatment modalities. The presented paper presents a review of some of the studies in the mitral valve disease story.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
(45 reference statements)
3
12
0
3
Order By: Relevance
“…Assessment of higher murmur in group B2 might be related to the progressive severity of the illnesses. It has been reported that the severity of DMVD in dogs was well associated with lower serum serotonin concentrations and higher LA/Ao which causes low serotonin concentrations (Ljungvall et al, 2014;Petric, 2015). The positive correlation between the cardiac auscultation (murmur) and LA/Ao (Table 3) can explain this result.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…Assessment of higher murmur in group B2 might be related to the progressive severity of the illnesses. It has been reported that the severity of DMVD in dogs was well associated with lower serum serotonin concentrations and higher LA/Ao which causes low serotonin concentrations (Ljungvall et al, 2014;Petric, 2015). The positive correlation between the cardiac auscultation (murmur) and LA/Ao (Table 3) can explain this result.…”
Section: Discussionmentioning
confidence: 75%
“…DMVD is the leading cause of cardiac disease in dogs throughout the world (Bonagura and Schober, 2009;Borgarelli et al, 2012;Terzo et al, 2009). Its prevalence has been found to be associated with breed, age and body size (Bernay et al, 2010;Borgarelli et al, 2004;Petric, 2015). Older small-breed dogs are predisposed (Petric, 2015).…”
Section: Introduction *Anatolianmentioning
confidence: 99%
See 2 more Smart Citations
“…Systolic heart murmur presented in chest auscultation. Systolic murmur at the mitral area is one of the characteristics of MMVD, which increases in intensity as the disease progresses (Petric 2015). Figure 1 shows 2D echocardiographic B-mode results in this dog was thickening and prolapse of mitral valve.…”
Section: ■ Results and Discussionmentioning
confidence: 84%